2020
DOI: 10.1002/ejlt.202000182
|View full text |Cite
|
Sign up to set email alerts
|

Bio‐Based Polymers Obtained from Modified Fatty Acids and Soybean Oil with Tailorable Physical and Mechanical Performance

Abstract: The impending world oil shortage, global climate changes, and environmental pollution encourage the use of natural renewable resources to produce substitutes for petroleum-derived polymers. In this work, two series of bio-based thermoset polymers are prepared by free radical polymerization of commercially available acrylated epoxidized soybean oil (AESO) with different amounts of methacrylated oleic (MOA) or lauric (MLA) acids. The characterization of the resulting cured bio-based copolymers is performed by in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 43 publications
1
5
0
Order By: Relevance
“…The same trend was observed in the work of Capiel et al 12 . and Hernández et al 20 . because the increase of STR in the copolymer modifies (increases) the amount of micro‐/nano‐gels formed during the first stages of curing and consequently also increases the amount of dispersion/reflecting zones with higher opacity values.…”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…The same trend was observed in the work of Capiel et al 12 . and Hernández et al 20 . because the increase of STR in the copolymer modifies (increases) the amount of micro‐/nano‐gels formed during the first stages of curing and consequently also increases the amount of dispersion/reflecting zones with higher opacity values.…”
Section: Resultssupporting
confidence: 83%
“…In this way, the ratio of the plant oil to reactive diluent can be conveniently adjusted to control the physical, mechanical and biodegradable properties of the polymerized plant derivatives 19 . Furthermore, this chemical modification route could give rise to polymer precursors and later to polymers, with β‐hydroxyester groups that can lead to associative exchange reactions when they are submitted to thermal treatments 20,21 . These new materials, called vitrimers, are being considered for their potential technological applications because they can exhibit outstanding properties like self‐healing and surface welding, network malleability and shape memory, amongst others 22,23 …”
Section: Introductionmentioning
confidence: 99%
“…The shape of water droplet on the sample surface is showed in Figure S7b, and the PG55‐1Im‐1 presented contact angle equal to 74.7 ± 0.5°, which did not differ significantly to other coating materials described in literature. For instance, Noè and collaborators achieved 74.9 ± 2.0° by photopolymerization (Type I) of EGSO and described it as an anticorrosion coating while polymers derived from ESO and methacrylated oleic or lauric acids in different proportions provided values between 70 and 86° 53,54 . In addition, Pawlak and coauthors reported contact angles between 66.4 and 80.8° for polymers obtained from maleinized vegetable oil and poly(lactic acid) 55 .…”
Section: Resultsmentioning
confidence: 99%
“…Polymer properties can also be controlled by changing the nature of the comonomer or the acrylated triglyceride, such as the use of acrylated epoxidized camelina oil instead of AESO to obtain a higher degree of functionality (Li & Sun, 2015). Renewable alternatives to styrene and divinyl benzene include methacrylated vanillyl alcohol (Chen, Liu, et al, 2020), methacrylated oleic and lauric acids (Hernandez et al, 2020), ethyl cellulose (Liu et al, 2021), and maleic anhydride (Lu et al, 2005), among others. AESO has also been combined with natural fibers and other fillers to produce composites with enhanced mechanical strength for automotive and construction applications (Liu & Tisserat, 2018; O'Donnell et al, 2004).…”
Section: Introductionmentioning
confidence: 99%